Ten-year comparison of the efficiency of legal regulations of foodborne pathogens in broilers in Türkiye - Buyukunal, SK; Muratoglu, K; Yilmaz Eker, F; Gjoni Gundemir, M; Topcuoglu, S; Koluman, A (Journal of the Hellenic Veterinary Medical Society, 2024)
Broiler meats are the primary source of foodborne pathogens, such as Campylobacter jejuni and Salmonella spp., and E. coli O157. The illegal use of antibiotics for preventive purposes or the habit of using broad-spectrum antibiotics in farms causes antibiotic resistance in these pathogens. This study compared C. jejuni, Salmonella spp. and E. coli O157 and their antibiotic resistance patterns in broiler meats in 2011-2012 and 2021-2022. The research we conducted in 2011-2012 to observe the effectiveness of the legal regulations enacted in Türkiye in 2014 and 2018 for controlling pathogens and monitoring the use of antibiotics was also repeated with a similar sample set in 2021-2022. The results showed the prevalence of C. jejuni, Salmonella spp., and E. coli O157 in 2011-2012 and 2021-2022 with 68.0%, 30.4%, 0.8% and 10.08%, 7.77%, 0.21%, respectively. The antimicrobial susceptibility tests against gentamicin, streptomycin, erythromycin, ciprofloxacin, enrofloxacin, tetracycline and oxytetracycline were performed by agar disk diffusion method. According to results in 2011-2012, all C. jejuni and Salmonella spp. were resistant to at least one tested antibiotic, with 31.57% Salmonella spp. and 16.47% C. jejuni being multidrug-resistant. In addition, one of the E. coli O157 strains was resistant to one antibiotic, and the other was resistant to two antibiotics. In 2021-2022, 81.3% C. jejuni, 46% Salmonella spp., and only one E. coli O157 were resistant to at least one tested antibiotic. Isolated strains of 8.33% C. jejuni and 21.62% Salmonella spp. were multidrug-resistant. In the past, antibiotics were used for preventative purposes, as indicated by the survey results. Today, it is evident that these rates have decreased to low levels as a result of legal regulations and monitoring.